(untitled) (International Journal of Engineering and Computer Science, 2014)
New forms of scholarship are emerging in the world. These aim at providing freely accessible research materials through scholarly communication. There are two common ways of providing open access to research outputs namely, through the open access journals and through discipline or institutional-based open access repositories, that is: Open Access Institutional Repositories (OAIR) driven by open access publishing. In principle, open access to research outputs maximizes research access and thereby also research impact, making research more productive and effective. Today, institutional repositories are becoming major components of the technical infrastructure of successful research–based institutions. It is a trend now observed in most universities and in particular research-based institutions in developing countries. Recently, there has been a high uptake of institutional repositories by higher learning institutions in Tanzania. Despite this fact however, the study on the status of open access publications in the country have not been undertaken. This paper provides an overview of characteristics of open access repositories as a global publishing concept. It then applies the same, as a case study, to review open access publications in Tanzania, and summarizes the status of a growing body of evidence on adoption and usage of open access publications in the country. It also assesses the contribution of Tanzanian institutional repositories in the scholarly communication. In the assessment, performance of Tanzanian institutional repositories, as reflected through global visibility and impact of their repositories in the Directory of Open Access Repositories (OpenDOAR), is examined. In addition, the performance of Tanzanian universities in archiving and sharing research findings through institutional repositories, based on the Ranking Web of Repositories (RWR) is examined. Findings from the examination of the identified open access repositories reveals that, out of the 5 Tanzanian institutional repositories in the study, only 2 are listed in the RWR. These two are ranked at 1060th and 1362nd positions (out of 1983) in the world ranks, as at July 2014. This implies that only 40% of the identified repositories in Tanzania are visible and incorporate good practices in their web publications. It is also revealed that much studies have focused not on open access institutional repositories, but on the factors contributing to adoption of open access scholarly communication in the country. Hence, the relevance of the research reported in this paper.